THE LOCAL WISDOMS IN THE KETOPRAKAN TRADITIONAL ART PERFORMANCE FROM TULUNGAGUNG AMPAK-AMPAK BRANG WETAN - PALEMBANG, NOER WINDHA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Local Wisdoms, Ketoprakan, Drama, Ampak-Ampak Brang WetanLocal wisdoms is the reflexsive of human activity which is formed after long period, passed through generation and created the character of the society, especially in Tulungagung. There are harmonous life among human being, environment and their beliefs to the God. The local wisdoms is represented in the traditional art performance ketoprakan from Tulungagung entitled Ampak-Ampak Brang Wetan story tells about the legend of the early beginning of Tulungagung Region. The purpose of this research is to find the manifestation of local wisdoms in the ketoprakan entitled Ampak-Ampak Brang Wetan.The researcher analyzed about the manifestation of the local wisdoms which is delivered in the ketoprakan using folklore approach. There is the ability from the society to develop an oral tradition which is passed through generation in to a new shape-traditional art performance ketoprakan. The local wisdoms in Tulungagung Society is delivered in a new way through the elements of drama in performance, such as plot, characters and satire comedy.According to the result of the analysis, the researcher found so many manifestation of the local wisdoms which is delivered in ketoprakan about Ampak-Ampak Brang Wetan. In the performance, there are three manifestation of the local wisdoms; human should respect each other, evironment and believe in God which later, guide them to create harmonous life.The researcher finds the local wisdoms in the performance later can be the powerful media to influence the societ y’s way of thinking in creat ing harmonous life. The researcher suggests the next researcher to dig more about the local wisdoms and the impact for the society since the researcher only focuses on how local wisdoms is manifested in the ketoprakan traditional art performance entitled Ampak-Ampak Brang Wetan.